Case Book for MS (Orthodontics) Part II - Basnayake, P.D.A.S (My University, 1991)
Class I crowding treated with removable appliance; Median diastema; Class I with rotation 21_I ; Class I with supernumerary tooth and dilacerated I_2 ; Class I with mesiodense and rotated I_1 ; Class I with translocated I_3 ; Class II division I treated with removable appliance; Class II division I treated with enmasse appliance; Class II division I treated with functional appliance; Class II division I treated by extraction of all four first premolars and begg technique; Class II division I treated with edgewise technique; Class II division 2 treated with removable appliance; Class II division treated with fixed appliance; Anterior crossbite ( mixed dentition treatment); Class III distalization of upper buccal segment to create space for 3_I_3; Class III with buccally placed 3_I_3 treated with fixed appliance; Class III treated with removable,fixed appliance; Class III treated with begg technique; Class III with cleft lip and palate; Class III with cleft lip palate treated with quadhelix appliance